“见证”的文本：《我怎样在敌人的刺刀下生活》的脉络化解读: Witnessing as Text: A Contextual Interpretation of How I Lived Under the Enemy’s Bayonets - See Hooi Min 施慧敏 (Journal of Sinological Studies 漢學研究學刊, 2024)
《圣经．约伯记》里有一句话：“我是惟一一个逃出来向你报信的人”。《我怎样在敌人的刺刀下生活》一文里，报信人没有报出自己的名字来历，却说了一个抗争的故事，成了记忆、历史和时代的“证言”。这是赵戎编《新马华文文学大系》（1971）散文集，陈大为和锺怡雯编的《马华散文史读本 1957-2007》（2007）一书，皆收录此文之因。“在阐述故事从何而来这个问题之前，必须先回答他是什么这个问题。”[1]作为文学里难得一见的女性抗战经历和题材，抗日的事迹是如何被叙述的？文章发表于何处，作者表达了怎样的意识型态与意图，经由什么成员阅读与想象，凝聚共同体意识？历史可能依据政权需求筛选过去，文学作为修复记忆的功能，有时候也会参与意识形态的建构，如此又如何以文证史？而女性被动地卷入战争，她的参与和表述，除了见证之外，是否也是时代和党派下的宏大叙事？本论文从失记的角度切入，探讨文本的再现机制，以及历史、文学、女性的可见与不可见。 In the Book of Job from the Bible, there is a line that reads: "I alone have escaped to tell you." In the essay "How I Lived Under the Enemy’s Bayonets", the messenger who delivers the story reveals neither name nor origin, yet conveys a tale of resistance that becomes a testimony of memory, history, and its time. This is why the piece was included in The Anthology of New Malaysian Chinese Literature (1971) edited by Zhao Rong, and later in A Reader in Malaysian Chinese Prose 1957–2007 edited by Chan Tah Wei and Chong Yee Voon (2007). “Before we can say where a story comes from, we must first ask what it is.” This essay—structured around a rare account of a woman’s experience during wartime—raises key questions: How is the anti-Japanese resistance narrated when framed through a female perspective? Where was the essay first published, and what ideological stance or intention does the author convey? Through whose reading and imagination did it help forge a sense of community consciousness? History may be filtered through the needs of state power, and while literature often serves the function of restoring memory, it can also participate in the construction of ideology. In such a dynamic, how can literature serve as testimony to history? Moreover, when women are passively drawn into war, is their participation and articulation merely testimonial, or does it also serve as part of the grand narrative shaped by party and epoch? This paper takes the perspective of erasure and forgetting as its point of departure to explore the representational mechanisms of the text, as well as the visibility and invisibility of history, literature, and women.